Music therapy microanalysis of parent-infant interaction in a three-month-old infant later diagnosed with autism - Ferdinando Suvini; Fabio Apicella; Filippo Muratori (Health Psychology Report, 2016)
Background Infant research literature has described for a long time the main aspects of parentese (motherese and fatherese) referring to musicality and specifically to musical language. It is believed that there is a deep analogy between the vital affects experienced by the child during interaction with the parent and the type of parentese that is a direct representation of them. Disruption of parentese has been described in early autism. The aim of this paper was to achieve a better understanding of this disruptive process.